Association of Increased Risk of Atherosclerotic Cardiovascular (ASCVD) Event in Chronic Liver Disease Patients with and without Cirrhosis - Hashemi, Leila; Wenziger, Cachet Magdolna; Do, Tran; Patel, Arpan; Pisegna, Joseph R; Ganz, Tomas; Budoff, Mathew; Gornbein, Jeffery; Elashoff, David; Streja, Elani (Cardiology and Cardiovascular Medicine, 2022)
Background: An area of debate in modern medicine is whether there is an association between cirrhosis and Atherosclerotic Cardiovascular Disease (ASCVD). To address this we conducted a retrospective cohort study composed of the 486,887 US Veterans with liver disease over the period of January 2000 to December 2019 to ascertain whether there is an association between cirrhosis and ASCVD. We further divided the cohort based on a diagnosis of cirrhosis. Cox-Regression, negative binomial and competing risk models were used to investigate the time interval between the first and recurrent ASCVD hospitalization with mortality as a competing event risk. The mean± SD age of the cohort was 58 ± 11 years, 4.6% were female, 63% White, 21% Black. 58% of the cohort had liver disease without a diagnosis of cirrhosis. The incidence of ASCVD hospitalization was much higher in liver patients with diagnosis of cirrhosis (11% vs 6%, p value<0.001). In a non-adjusted model with cirrhosis as the exposure the rate of first ASCVD hospitalization was 1.5 times higher than liver disease in patients without cirrhosis (HR: 1.49 (95%CI: 1.47- 1.50), p <0.001). In a fully adjusted model, the risk was attenuated but remained statistically significant (HR: 1.03 (95% CI:1.02-1.04, p <0.001)). The mean number of ASCVD hospitalizations in a count model was 30% lower in the cirrhosis group (mean count ratio 0.70 (95% CI: 0.68-.072)), due to higher competing risk of all-cause mortality with ASCVD events (0.77 (0.73-0.81)). Conclusion: We demonstrate in this retrospective cohort study that as liver disease progresses to cirrhosis, the risk of ASCVD events increases. We hypothesize that the pro-inflammatory states of liver disease could be a viable explanation for the increased risk of ASCVD events in cirrhosis patients. Further translational studies are needed to confirm this hypothesis.